G186(P) The swim drink study: A randomised controlled trial of during-exercise rehydration to enhance performance. (24th May 2017) - Briars, GL; Gordon, GS; Lawrence, A; Turner, A; Perry, S; Pillbrow, D; Walston, FE; Molyneux, P
Abstract : Sports drinks are widely used with the aim of improving hydration and performance, but the supporting evidence for claims of enhanced performance has not been of high quality. There are however clear health risks from overhydration. Aims: To answer 3 questions: Does drinking during swimming Improve performance? Is isotonic sports drink better than water? Are there idiosyncratic responses in individual swimmers? Method: 19 competitive swimmers aged 11–17 drank ad-libitum sports drink (x3 sessions), Water (x3 sessions) or no drink (x6 sessions) in the course of twelve 75 min training sessions, each followed by ten 100m maximum effort freestyle sprints at 3 min intervals. Electronic timing equipment recorded times for the middle 50m of each sprint. Each athlete used the rehydration regimes in an individually randomised order and was blinded to drink allocation. To blind the observers a block randomised analysis subset of data from 8 sessions was selected after data collection. Percentage dehydration was determined from weight measurements. Repeated measures t-tests assessed primary outcome measures. Results: The analysis data comprised 1118 swims. Sprint times after not drinking were 0.027 s faster than after drinking (95% CI 0.186s faster to 0.113s slower). Times after drinking water were 0.151s faster than after sports drink (95% CI 0.309s faster to 0.002s slower) There was no performance difference between drinking regimes. Mean (SEM) 50 m time for no drink swims was 38.077 (0.128)s and 38.105 (0.131)s for drink swims, p=0.701. Mean 50m times were 38.031 (0.184)s for drinking water and 38.182 (0.186)s for drinking sports drink, p=0.073. No individual athlete had progressive performance improvement with drinking water and sports drink. The exercise generated 0.42% dehydration which was over-corrected by drinking to +0.27%. Conclusions: Drinking sports drink or water over 105 min of sustained effort swimming (typically 3300 to 4200m) has no benefit on swimming performance in a non-elite athlete population. Sports drinks can be considered as sugar sweetened beverages.